STUDI KOMPARATIF ANALISA HARGA SATUAN PEKERJAAN STRUKTUR BETON ANALISA PROYEK, METODE KONDISI AKTUAL, SNI 2016 DAN PERMEN PUPR NO. 1 TAHUN 2022 MENGGUNAKAN SOFTWARE ESTIMATOR.ID - Made Wena, Egi Yusriatur Rahmadani (BANGUNAN, 2021)
Abstract: Delays occurred in the Accounting and Commerce Administration Building Construction Project Phase I, Malang State Polytechnic, Malang City on 29 June 2021 to 26 July 2021, originally the cumulative weight on the initial S-curve plan was 17.39%, but in practice it was only achieved 7.73% in the 1st floor of structure work. The delay was due to the need for materials that should have been able to reach the field’s target was not facilitated, due to a discrepancy in the planning analysis with the standardized Work Unit Price Analysis (AHSP) guidelines, so it was necessary to evaluate comparison of AHSP according to project analysis, actual condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022 in order to find out the most appropriate type of method as a reference in conducting planning analysis. Calculations on concrete structure work because it has a major influence on the cost of construction projects. The purpose of the research are: (1) Describing the total unit price of concrete structure work project analysis, Actual Condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022software Estimator.id, (2) Describing the largest unit price percentage ratio of concrete structure work between project analysis of Actual Condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022, (3) Describing the lowest percentage ratio of the total unit price of concrete structure work AHSP method, (4) Knowing the level of distribution of tests together with the unit price of concrete structure work project analysis, Actual Condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022and (5) Knowing the level of distribution of paired tests of unit prices of concrete structure work project analysis, Actual Condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022. The design of research using descriptive, comparative research, experiments with quantitative approaches. Secondary data collection using research instruments in the form of documentation guidelines. Data analysis was carried out by calculating the AHSP of the three methods and then the ANOVA One Way test for comparison together and Tukey HSD for the comparison test in pairs. The results of the study are: (1) HSP total of concrete structure project analysis of IDR 252,161,551.51, Actual Condition method of IDR 296,562,918.52, SNI 2016 of IDR 300,278,528.99 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022 of IDR 295,731,973.03, (2) the largest percentage ratio between the Actual Condition method, SNI 2016 and Regulation of Minister of Public Works And People’s Housing Number 1 of 2022 to project analysis is plate foundation work with a consecutive ratio value of 0.301%, 0.283% and 0.268%, (3) the lowest total HSP percentage ratio is the Regulation of Minister of Public Works And People’s Housing Number 1 of 2022 with a ratio value of 0.147%, (4) the results of the comparison test with ANOVA One Way, namely there is a significant difference with a significance value of 0.03 < 0.05, and (5) the results of the comparison test in pairs of Tukey HSD, namely there is a significant difference between the AHSP project analysis and the SNI 2016 method with a significance value of 0.043 < 0.05.Keywords: Job Unit Price Analysis, Coefficient, Unit Price of Work